Corporate Financial Risk Management in China’s Financial Markets: Strategies and Practices - zhang, chong (Pacific International Journal, 2024)
This research paper explores the realm of corporate financial risk management within the dynamic context of China’s financial markets. Focusing on market risk, credit risk, and operational risk, the study examines the strategies and practices employed by industry leaders, including Ping An Insurance, Alibaba Group, and Tencent Holdings. Through a combination of case studies and insights from interviews with key personnel, the research elucidates the multifaceted approaches these companies employ to mitigate financial risks. The analysis highlights the critical importance of technological innovation, robust governance frameworks, and a proactive risk-aware culture in navigating the complex landscape of financial risk management in China.